Minhaj Al-Qashi Died After (782 AH) In the Chapters of the Sciences of the Qur’an - Zernan, Moheb El Din; Youssef , Ismail (Islamic Sciences Journal, 2023)
This research aims to find out the methodology that Bahaa AL Deen ALQashi (May Allah have mercy on him) followed it in the chapters of the Quran sciences. The researches of the sciences of the Quran are from the researches that Al Qashi has exposed them at the beginning of his discussion on the first division (Precedents and Introductions) . I found that the chapters of the Quran sciences are dispersed and among them the virtues of the Quran, as well as jurisprudential and doctrinal researches that are related to reading of the Quran. His method depends on the original tabulation without finding sub tabulation except for the headings of the chapters. That methods leads me to study the chapters of Quran sciences and orders them and shows his approach in them. This interpretation that is called (The Adopted transmission from what was revealed to the Messenger) , (Peace and bless upon him), is from the rare interpretation which deal with the Hadith and the narrated traces from the Messenger (peace and bless upon him), the companions and the followers. Has been kept away from transmitting the anomalous traces and the interpretation by opinion and this is what makes it unique of his gender that prompted me to study his method. I ask my Almighty Allah to grant me success.